Biomass energy: a review on waste to energy approaches - Yoke, Wang Cheng; Cheng, C. K. (Universiti Malaysia Pahang, 2018)
Although Malaysia is blessed with significant reserves of fossil fuels, the crisis of these non-replenishable energy resources is foreseen with escalating human population. Fortunately, Malaysia is an agroindustry-based country while transforming into a manufacturing-based country. It is believed that the tremendous biomass waste sourced from various industrial sectors could be ameliorated into renewable biomass energy. Therefore, this paper reviews four major approaches that facilitate the conversion of biomass waste into energy, particularly gasification, fast pyrolysis and liquefaction, transesterification, and hydrolysis. It is worthwhile to declare that these pathways generate energy and mitigate environmental issue concurrently.